Popular Consultation on oil exploitation in the Yasuní ITT as resistance to the National development plans in Ecuador - García-Orellana, Diana; Siguenza-Orellana, Sonia (DICERE Revista de Derecho y Estudios Internacionales, 2024)
This article addresses James Scott's reflection in his book published in 1998 'Seeing like State' on why the great development plans generated by the state end up failing? For Scott, the main characteristic is that they are western modernist and technological projects. He emphasizes that he is not against technology or modernity, but rather the way in which the central state implements it in societies with notions different from Westernism and with a disdain for local knowledge. For that reason, the community organization creates resistance, and these plans usually fail. Finally, an analogy is made of this reflection with the large extractive oil projects in the Ecuadorian Amazon that are implemented in favor of Western development, but fail because they generate greater dispossession, protest, deterritorialization and loss of local culture. A form of resistance to these extractive projects is reflected in the favorable vote for the popular consultation on the exploitation of the Yasuní ITT last October 2023.